A Rare Case of Post-herpetic Keloid as Wolf’s Isotopic Phenomenon - Gurung, Tsering Dolma; Gupta, Pooja; Gurung, Maya (Nepal Journal of Dermatology, Venereology & Leprology, 2026)
Wolf’s isotopic phenomenon is the occurrence of a different skin disease at the same site where another skin disease had healed. It has been most commonly reported at the healed herpes zoster site. Development of keloids after healing of herpes zoster as an isotopic phenomenon is an uncommon response. Timely recognition of this phenomenon can prevent unnecessary interventions and promote early appropriate management.